DARI INTERNET MENUJU INTERVENSI: LITERASI DIGITAL SEBAGAI TAMENG KESEHATAN MENTAL PEMUDA PEDESAAN - Arya Fendha Ibnu Shina; Nur Fitriyani Hardi; Ferra Puspito Sari (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2025)
The high rate of internet penetration among young people poses a challenge for many stakeholders, given the potential for unhealthy internet-related behaviors, including internet addiction and smartphone addiction. Excessive internet use has a negative impact on the mental health of young people. Digital literacy is a necessary competency for internet users in this digital era. Young people are the backbone of the nation. One youth organization that contributes to national development at the village level is Karang Taruna. Karang Taruna Birawa in Dusun Sawangan is one such youth organization that has made significant contributions to both the local community and the Sawangan Village government.The aim of this study is to analyze the role of digital literacy in minimizing the negative impact of internet and smartphone addiction on the mental health of the youth in Birawa Sawangan. The findings indicate that digital literacy has the potential to act as a moderating variable that weakens the influence of internet addiction on mental health. Although digital literacy still has a significantly positive effect on mental health, it does not weaken the influence of smartphone addiction on mental health. Therefore, targeted interventions are needed to address smartphone addiction. Keywords: smartphone addiction, internet addiction, digital literacy, young generation.